Pengaruh Implementasi Sistem Pelaporan Akuntansi Sektor Publik dan Pengendalian Internal terhadap Akuntabilitas Kinerja Pemerintah Kabupaten Nagan Raya - Alfiaturrahmi, Alfiaturrahmi; Maulina, Rina; Mahdani, Said (Medan Resource Center, 2024)
This study examines the influence of public sector accounting reporting implementation and internal control on government performance accountability at the Regional Financial Management Agency of Nagan Raya Regency. The research is motivated by recurring delays in financial report submission, which reflect weaknesses in the application of public sector accounting systems and internal control mechanisms, including ineffective planning processes, non-compliance with revenue management regulations, and policy implementation that contributes to increased public expenditure. Employing a quantitative research design, this study involved 57 employees as respondents selected through a census sampling approach. Data were analyzed using validity and reliability tests, simple linear regression analysis, normality testing, t-tests, and coefficient of determination analysis. The findings reveal that the implementation of public sector accounting reporting and internal control simultaneously exerts a significant effect on government performance accountability, as indicated by a significance value of 0.000. These results demonstrate that stronger accounting reporting practices and more effective internal control systems enhance the accountability of public sector performance. The study concludes that improving institutional compliance with public sector accounting standards and strengthening internal control structures are essential for reinforcing government accountability and ensuring transparent and responsible financial governance.